Efektivitas Pelatihan Standar Operasional Prosedur (SOP) terhadap Kompetensi Kerja Karyawan - Nur Ramadhan Setyabudi; Lingga Yuliana (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study aims to analyze the effectiveness of Standard Operating Procedure (SOP) training on improving employee work competencies at PT Prima Sejati Sejahtera, a manufacturing company located in Central Java. SOP training that is organized in a structured and routine manner is expected to improve the quality of employee performance in accordance with applicable operational standards. This research uses a qualitative approach with data collection techniques in the form of in-depth interviews with employees involved in SOP training. The results of the study showed challenges such as unequal understanding between employees, time constraints, lack of in-depth interaction during training. Nonetheless, the training was still influential in improving employee competence and performance, although there were some barriers that affected its effectiveness. Therefore, the company needs to evaluate and improve the training materials, methods, and time so that it can be more optimal in improving the quality of employee performance.